2022
DOI: 10.4491/eer.2021.522
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of Trema orientalis wood biochar using natural coconut vinegar and its potential to remove aqueous calcium ions: column and batch studies

Abstract: Recent investigations have revealed the harmful health effects of elevated calcium levels in drinking water. Chemically activated biochar is the most popular option for low-cost cation adsorption. However, most of these chemicals are hardly available for rural communities, corrosive, and difficult to handle by unskilled personnel. This study aimed to determine the ability of natural coconut vinegar, a common mild acid, to activate Trema orientalis wood biochar pyrolyzed at 300ºC (BC) as a facile, safe, and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The experimental adsorption capacity could be greater due to the multilayer physical adsorption. Authors of this study have previously reported the effective use of vinegar-activated biochar in reducing water hardness [11,12]. To our knowledge, no previous studies have reported the adsorption of MB onto Trema orientalis wood biochar or any other form of vinegar-activated biochar.…”
Section: Adsorption Isotherms and Kineticsmentioning
confidence: 81%
See 4 more Smart Citations
“…The experimental adsorption capacity could be greater due to the multilayer physical adsorption. Authors of this study have previously reported the effective use of vinegar-activated biochar in reducing water hardness [11,12]. To our knowledge, no previous studies have reported the adsorption of MB onto Trema orientalis wood biochar or any other form of vinegar-activated biochar.…”
Section: Adsorption Isotherms and Kineticsmentioning
confidence: 81%
“…Dried wood pieces were slow pyrolyzed (300。C, 2 h) under limited oxygen conditions in a household kiln. Pyrolyzed product was washed with deionized water, dried in an oven (80。C, 12 h), and ground to powder (< 0.5 mm) [12]. It was tagged as WB.…”
Section: Preparation Of Biocharmentioning
confidence: 99%
See 3 more Smart Citations